PERILAKU BIROKRASI PADA KANTOR KECAMATAN PARIGI BARAT KABUPATEN PARIGI MOUTONG - Rislan, Rislan (Katalogis, 2016)
Abstract The main focus of the research is bureaucracy behavior. The research aims at finding out bureaucracy behavior at district office Parigi Barat of Parigi Moutong Regency. Theory used was from Miftah Thoha formulated in 5 aspects, as the main requirement of behavior achievement success, namely: ability, needs, trust, experience and expectation. This research employed a qualitative method. The informant was determined through purposive sampling. The data were collected through observation, interview and documentation. The techniques of data analysis were data reduction, data display and drawing conclusion (verification). The results reveal that bureaucracy behavior at district office Parigi Barat of Parigi Moutong Regency have not been felt and conducted as it should be by the apparatus of bureaucracy of district office Parigi Barat. From 5 aspects observed, three of them have not been done, namely ability, needs and trust. On experience aspect, evaluation given by the leader then it would make the apparatus pleased to work. In addition, on expectation aspect that it truly gives positive result even though there is still a bit of friction of bureaucracy. Meanwhile, three previous aspects were not good. On ability aspect, it gives a disappointed result where the absence or inactive of apparatus were still low and it impacted to individual behavior. On needs aspect, it was not fully fulfilled particularly on organic officers, whereas on trust aspect there are still any officers who did not understand their duty and function as bureaucracy apparatus so it would distract the improvement of behavior.